The Impact of Digital Transformation on Traffic Function (LANTAS) for the Development of the Banyuwangi Police Institution - Rico Darmawan; Noel Morado Pratama Simatupang; Fajar Islam; Syalsabela Wahyu Kurnia (People and Behavior Analysis, 2026)
Digital transformation has become an urgent need in various sectors, including within the Police Institution. In the current digital era, new challenges have emerged regarding the technical function of the Police, namely the traffic function, such as handling increasingly complex traffic order violations and adapting to the public's still limited understanding of information about public services for road users. This research aims to identify and analyze the impact of digital transformation on the technical function of the police, thereby increasing traffic operational efficiency and community satisfaction in Banyuwangi, and improving the performance of the Police Institution in Banyuwangi. The research was conducted using descriptive qualitative methods, where data were collected through in-depth interviews with members of the Police and road users in the field. It is hoped that a good understanding of the changes that occur due to the adoption of technology in traffic services can be obtained. The results of the research show that digital transformation has had a significant positive impact on operational functions, including the implementation of e-ticketing with CCTV-based surveillance cameras to improve traffic management. Interaction between the police and the public has become more open thanks to social media platforms used for two-way communication. The conclusion of this research confirms that digital transformation is not just a technological trend but a necessity to improve the quality of public services.